Analysis of Business Partnership Network Mapping: A Case Study of The Inovac Cooperative in Banda Aceh City - Indra, Indra; Athaya, Putri; Zikri, Irfan; Nugroho, Agus (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2024)
Inovac Cooperative is a business entity engaged in expanding and marketing innovative products. Inovac has cooperative relationships with various parties. Obtaining communication interactions and having reliable service is essential to the success of the cooperative. This study aims to determine the pattern and network map between partners that have the most role in the sustainability of the Inovac cooperation. The analysis method used is Social Network Analysis (SNA). This research was conducted from February to April 2022. The results show that the network density in the cooperative relationship is 58%, where the network density can be categorized as quite strong. In addition, three (3) forms of cooperation network patterns and maps were obtained using Ucinet/Netdraw software: Degrer Centrality, Betweenness Centrality, and Closeness Centrality. The most dominant actors are ARC, UD. Ivone, BI, Diskop, Disperindag, Bappeda, and Patchouli Farmers. The results obtained can be used as a benchmark for Inovac cooperatives in continuing new collaborations with various partners